1997
DOI: 10.1007/s00585-997-1111-1
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and limitations of MST radar measurements of middle-atmosphere winds

Abstract: Abstract. Radars have been used successfully for many years to measure atmospheric motions over a wide range of altitudes, from ground level up to heights of several hundred kilometres into the ionosphere. In this paper we particularly wish to concentrate on the accuracy of these measurements for winds in the middle atmosphere (i.e. 10±100-km altitude). We begin by brie¯y reviewing the literature relating to comparisons between radar methods and other techniques. We demonstrate where the radar data are most an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…For more on the e ects of group retardation and estimates on real heights, we refer readers to Namboothiri et al (1993). The data from altitudes near 100 km may further be contaminated by E-region echo spreading (Hocking, 1997). These constraints must bear in mind when dealing the results from the uppermost altitudes (96 -98 km).…”
Section: Observations and Analysis Of Datamentioning
confidence: 99%
“…For more on the e ects of group retardation and estimates on real heights, we refer readers to Namboothiri et al (1993). The data from altitudes near 100 km may further be contaminated by E-region echo spreading (Hocking, 1997). These constraints must bear in mind when dealing the results from the uppermost altitudes (96 -98 km).…”
Section: Observations and Analysis Of Datamentioning
confidence: 99%
“…Because of the long tail on the Gaussian transmitter pulses used, and the steep gradient in returned power in height approaching the E region, height gates well away from the height of the total reflection layer may be contaminated by returns from the E region, possibly making the derived winds unrepresentative, and potentially unusable. This was first suggested by Hocking (1997) in the context of finite receiver bandwidths and who suggested that this was most likely to be an issue around mid-day. He suggested that all data over a measured height of 92 km should be discarded and repeated this in a subsequent review (Hocking 2011).…”
Section: Choice Of Operating Frequencymentioning
confidence: 95%
“…Reid (1996) reviewed MF techniques in terms of their ability to make measurements of mean winds, atmospheric tides, and gravity waves, and Hocking (1997) considers the strengths and limitations of mesosphere stratosphere troposphere (MST) radar measurements of middle atmosphere winds with a focus directly related to MF and HF radar techniques. Reid et al (1995) and Holdsworth andReid (2004a, 2004b) provide an overview of the capabilities of the BPMF radar which serves as a good description of the capabilities of MF/HF radars generally, provide a good description of a modern all-sky meteor radar, Fraser (2005) provides a history of the development of scientific radar in New Zealand very relevant to this review, and Hocking (2011) provides a general review of radar techniques for investigating the MLT region.…”
Section: Currentmentioning
confidence: 99%
“…Methods have been developed in wind field measurements using radars [1] such as spaced antenna (SA), Doppler beam swing (DBS) and spaced interferometry (SI). Two techniques (full correlation analysis [2] and full spectral analysis [3]) used in data processing are based on these methods.…”
Section: Introductionmentioning
confidence: 99%
“…2 The methods in wind measurements and atmospheric backscatter model 2. 1 The methods in wind measurements [1,6] 2.1.1 Doppler beam swing With three or more narrow beams pointing to several directions, at least three signals can be received and their autocorrelations (r(t)) are defined as follows…”
Section: Introductionmentioning
confidence: 99%